Contemporary cases in U.S. foreign policy : from terrorism to trade / Ralph G Carter - Carter, Ralph G.
Competing to shape US foreign policy, many actors - from the president and members of Congress to interest groups, NGOs, and the media - influence policy outcomes and subsequent implementation. This title examines the global financial crisis, US-Russian relations, Somali pirates, and the US economic embargo against Cuba.